2021
DOI: 10.1142/s0219622021500164
|View full text |Cite
|
Sign up to set email alerts
|

An Efficient Decision-Making Approach for Short Term Indoor Room Temperature Forecasting in Smart Environment: Evidence from India

Abstract: “Smart cities” start with “Smart Buildings” that improve the quality of urban services while ensuring sustainability. The current scenario in India reveals that the corporate and residential building structures are incorporating various self-sustainable techniques. Out of the multiple factors governing the comfort of smart buildings, indoor room temperature is an important one, since it drives the need of cooling or heating through controlling systems. Around one-third of total energy consumption of commercial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…MAPE obtained from ARIMAX and BDM models were 0.19 and 0.04, respectively. Pandey et al (2021) used BDMs for IRT forecasting where past historical indoor temperature datapoints and residuals were used as explanatory variables. Using test data set, BDMs were reported to have MSE, MAE and MAPE values as 0.751, 0.692 and 1.848, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…MAPE obtained from ARIMAX and BDM models were 0.19 and 0.04, respectively. Pandey et al (2021) used BDMs for IRT forecasting where past historical indoor temperature datapoints and residuals were used as explanatory variables. Using test data set, BDMs were reported to have MSE, MAE and MAPE values as 0.751, 0.692 and 1.848, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Mateo et al (2013) obtained the best MAE (0.111) using MLP + nonlinear autoregressive exogenous model (NARX). Pandey et al (2021) used hybrid models and BDM–ANN was reported to be the best fit model with MSE, MAE and MAPE values as 0.310, 0.398 and 1.031, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations